2020
DOI: 10.1158/1940-6207.capr-18-0262
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIa Trial of Metformin for Colorectal Cancer Risk Reduction among Individuals with History of Colorectal Adenomas and Elevated Body Mass Index

Abstract: ◥Obesity is associated with risk of colorectal adenoma (CRA) and colorectal cancer. The signaling pathway activated by metformin (LKB1/AMPK/mTOR) is implicated in tumor suppression in Apc Min/þ mice via metformin-induced reduction in polyp burden, increased ratio of pAMPK/ AMPK, decreased pmTOR/mTOR ratio, and decreased pS6 Ser235 /S6 Ser235 ratio in polyps. We hypothesized that metformin would affect colorectal tissue S6 Ser235 among obese patients with recent history of CRA. A phase IIa clinical biomarker tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Zell JA et al [ 83 ] recently reported the results of a phase IIa trial of metformin for CRC risk reduction in patients with elevated BMI and positive history of colorectal adenomas. Thirty-two patients were treated, with a baseline BMI of 34.9.…”
Section: Resultsmentioning
confidence: 99%
“…Zell JA et al [ 83 ] recently reported the results of a phase IIa trial of metformin for CRC risk reduction in patients with elevated BMI and positive history of colorectal adenomas. Thirty-two patients were treated, with a baseline BMI of 34.9.…”
Section: Resultsmentioning
confidence: 99%
“…A phase 3 clinical study demonstrated that significant CRA reduction was achieved by the administration of low-dose metformin in patients without diabetes (Higurashi et al, 2016). However, another phase IIa trial reported that metformin did not reduce rectal mucosa pS6 or Ki-67 levels in obese patients with adenomas (Zell et al, 2020). These seemingly contradictory results suggested the complexity of mechanisms underlying metformin treatment and prevention for CRA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of metformin to suppress polyp formation and proliferation in the rectal mucosa of nondiabetic, obese patients with a history of colorectal adenoma has been unsuccessful to date [ 23 ]. Furthermore, a subanalysis from the large scale Three or Six Colon Adjuvant (TOSCA) trial found that neither metformin use nor DM status were associated with survival outcomes in colorectal patients receiving adjuvant chemotherapy post-resection [ 24 ].…”
Section: Metformin In Cancermentioning
confidence: 99%